EP.TU.693A rare case of anal melanoma: An entity to be aware of. (28th October 2021) - Dhaif, Ahmed; Boyle, Cameron; Lowe, Katherine; Paterson, Rosemary; Gumber, Ashutosh
Abstract: Aims: Anal melanoma is a rare but aggressive malignancy representing a small percentage anorectal cancers. We report a rare case incidentally detected during bowel screening. Methods: A 74-year-old female presented for endoscopy after a positive qFIT. She was asymptomatic. During endoscopy, perianal examination revealed a jet black naevus of approximately 3x3cm from 9 to 12'O clock position, overlying the perianal body, involving anal margin to the posterior vagina. General physical, abdominal and rectal examinations were unremarkable. During colonoscopy, a benign polyp was removed from the sigmoid colon. She underwent examination of rectum and vagina under general anaesthetic, and incisional biopsies were obtained. Histopathology confirmed an invasive, superficial spreading malignant melanoma, with a Breslow thickness of 1.5mm and Clark Level IV invasion. Staging CT scans did not reveal metastasis. Following loco-regional MDT discussion, a combined colorectal and plastic surgery was offered. She underwent wide local excision from the posterior vaginal fourchette to the anal canal, bilateral perforator flap reconstruction, and defunctioning sigmoid loop colostomy. Results: There were no intraoperative complications. She recovered well post-operatively. After histopathology, her tumour was staged as pT2b, N0, M0. She did not require further treatment post-operatively as per MDTdiscussion. No disease recurrence has been detected yet with 30 months follow up, and she is awaiting reversal of colostomy. Conclusions: Prognosis is generally poor in anal melanoma. This case report adds to the limited literature and emphasizs that despite no consensus on management, early detection and surgical resection offers the best chance for favorable outcomes.